olk creativity. Between the pleasure of the lips and the power of writing - abdelaziz, nacer (El Omda in Linguistics and Discourse Analysis, 2023)
Popular creativity in its entirety is oral speeches, or the product of two sides of the mouth: a producer and a consumer (delivered and received) are characterized by popularity. According to the opinions of the vast majority of its scholars, both parties contribute to the creative production process, and one party is not exclusive to it without the other, as is the case in the literature of subjects/privileged subjects, where there is no (direct) connection between its two ends (the author/reader). Because the recipient does not exercise any influence on the recipient, and then there is no (direct reaction) as long as the process of sending creativity is complete and finished before it reaches the audience of his readers. A tale of a fierce rivalry between lips and writing and a heated debate between supporters of public creativity and private literature. This research will stand the position of the scrutinizing student.